Data in Schools: (Changing) Practices and Blind Spots at a Glance - Krein, Ulrike; Schiefner-Rohs, Mandy (Frontiers in Education, 2021)
This review aims to provide a concise overview of the role of (digital) data and new data practices in schools. By focusing on the impact of data on pedagogical practices, it aims to shed light on how the everyday tasks of teachers and other pedagogical staff in schools are changing, particularly as a result of the generation and use of digital data. For this purpose, existing studies and previous theoretical debates on this topic are examined for their perspectives on data and data practices in schools. The pedagogical data practices of (improving) teaching and learning, assessment and counseling, (data-driven) decision-making, and cooperation and collaboration by “doing data” will be elaborated and discussed. Likewise, data practices that are missing from the studies are identified. We conclude with an overview of blind spots and further research needs.